Where is the most feasible, economical, and green wind energy? Evidence from high-resolution potential mapping in China. (20th November 2022) - Wang, Yanhua; Qin, Yanyue; Wang, Ke; Liu, Junling; Fu, Sha; Zou, Ji; Ding, Li
Abstract: China has ambitious renewable energy development plans after undergoing a rapid development phase for wind power. China's prospects for wind development affect the global decarbonization path. The question of where to deploy turbines of this magnitude to achieve technical feasibility, high economic competitiveness, and high emission reduction has become an urgent issue for China. Due to regional differences in wind resources and economic development, the deployment of wind power in China requires clarity on the likely siting and investment costs. It requires an accurate assessment of the exploitable possibilities of wind energy resources in China, which provides practical solutions for national and regional wind energy development. In this study, a multi-potential assessment was developed to estimate the feasibility and emission reduction contribution of wind power using a combined GIS-based approach and learning curves. It is found that there are large areas of land and ocean available for wind farms in China, especially the desert in the northwest and the coastal area of Fujian province. The technical potential of onshore and offshore wind power is 8650.33 TWh/yr and 11298.9 TWh/yr, respectively. Moreover, 76.06% and 20.69% of onshore and offshore wind, respectively, could be supplied economically. The optimal areas for building onshore wind by 2030 are located in Inner Mongolia, Gansu, and Xinjiang, while the optimal construction area for offshore wind power is mainly the coastal area of Fujian. Wind energy has a large potential to meet China's electricity demand and is set to be more cost-competitive as time passes. The cost of onshore and offshore wind will decrease by 25–53% and 21–46%, respectively, by 2030. Wind development could contribute 7823.73–10723.50 Mt CO2 reduction during 2021–2030, which could help decarbonize China's energy system. Highlights: A multi-potential assessment is developed to estimate the feasibility and emission reduction of wind power. China's onshore and offshore wind generation could reach 8650 TWh/yr and 11299 TWh/yr respectively. 76.06% of onshore and 20.69% of offshore wind energy can be supplied economically. Northwestern China was the most optimal option for wind power operation. China's wind energy deployment could cut carbon emissions by 7824–10724 Mt CO2 in 2021–2030.